Suggested Model for auditing the performance of municipal institutions to verify the services provided (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The services provided by the municipal institutions of the basic things needed by the man in his daily life and the evolution of cities basically depends on these services and therefore has paid most of the world's attention to this vital facility and give him the biggest concern for the welfare of the citizens, as is the research problem that there is no program scrutiny to evaluate the performance of municipal institutions contribute to measuring the efficiency and effectiveness of the services provided and was based on research on the premise that the preparation of the existence of audit program to evaluate the performance of municipal institutions contribute to measuring the efficiency and effectiveness of services provided has reached the researchers to a set of conclusions the most important of the Office of financial supervision federal program does not cover all activities and the activities of municipal institutions. The study came out a set of recommendations from the specimen, notably the adoption of the proposed program of auditing the municipal financial institutions and the obligation) to measure the progress made in the provision of municipal services and stand on the obstacles to achieve the desired goals.